Project on Human Development in Chicago Neighborhoods (PHDCN): Physical Development Scale, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. The Physical Development Scale was a self-report measure consisting of items that were used to ascertain pubertal status for children in Cohorts 6, 9, and 12. In Wave 1, this was interviewer administered and was referred to as the Pubertal Development Scale (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): PUBERTAL DEVELOPMENT SCALE, WAVE 1, 1994-1997 [ICPSR 13595]). In Wave 2, this was self-administered (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): PHYSICAL DEVELOPMENT SCALE, WAVE 2, 1997-2000 [ICPSR 13645]).